2008
DOI: 10.1073/pnas.0710902105
|View full text |Cite
|
Sign up to set email alerts
|

Opioid neuropeptide genotypes in relation to heroin abuse: Dopamine tone contributes to reversed mesolimbic proenkephalin expression

Abstract: Striatal enkephalin and dynorphin opioid systems mediate reward and negative affect, respectively, relevant to addiction disorders. We examined polymorphisms of proenkephalin (PENK) and prodynorphin (PDYN) genes in relation to heroin abuse and gene expression in the human striatum and the relevance of genetic dopaminergic tone, critical for drug reward and striatal function. Heroin abuse was significantly associated with PENK polymorphic 3 UTR dinucleotide (CA) repeats; 79% of subjects homozygous for the 79-bp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 43 publications
2
64
0
Order By: Relevance
“…Nevertheless, future studies involving larger populations will help clarify these issues especially in relation to novelty-seeking traits and allow the possibility to examine other markers specifically enriched in VSM neurons. Moreover, although we focused on the 3′UTR based on our initial hypothesis, other polymorphisms of PDYN within the promoter region have also been shown to be relevant for gene expression (Zimprich et al, 2000;Nikoshkov et al, 2008) and in relation to substance abuse (Ray et al, 2005;Clarke et al, 2012;Saify et al, 2014). The contribution of different variants within the PDYN gene to discrete behaviors needs to be addressed in larger populations that would provide the statistical power to examine such questions.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, future studies involving larger populations will help clarify these issues especially in relation to novelty-seeking traits and allow the possibility to examine other markers specifically enriched in VSM neurons. Moreover, although we focused on the 3′UTR based on our initial hypothesis, other polymorphisms of PDYN within the promoter region have also been shown to be relevant for gene expression (Zimprich et al, 2000;Nikoshkov et al, 2008) and in relation to substance abuse (Ray et al, 2005;Clarke et al, 2012;Saify et al, 2014). The contribution of different variants within the PDYN gene to discrete behaviors needs to be addressed in larger populations that would provide the statistical power to examine such questions.…”
Section: Discussionmentioning
confidence: 99%
“…Opioid gene signaling is a critical link in a number of human behavioral responses [reviewed in Sonetti et al, 2005;Bodnar, 2009;Stein and Zollner, 2009], as well as in many human disease susceptibilities [Kreek, 1996a;Ogden et al, 2004;Kreek et al, 2005;Drakenberg et al, 2006;Kennedy et al, 2006;Xuei et al, 2006Xuei et al, , 2007Huang et al, 2008;Nikoshkov et al, 2008;Bodnar, 2009]. Several studies have presented evidence of functional changes that have occurred in the coding sequences of these genes, both across vertebrate evolution [Dores et al, 2002;Stevens et al, 2007;Dreborg et al, 2008] and within human populations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A further challenge will be to understand the polymorphisms in the regulatory regions that have become fixed between species that might be driving differences in expression. To date, several studies have investigated the functional impact of regulatory variants of the PDYN gene [Zimprich et al, 2000;Nikoshkov et al, 2005Nikoshkov et al, , 2008Yuferov et al, 2009;Babbitt et al, 2010b] and OPRM1 [Shabalina et al, 2009] within human populations. There are also OPRM1 coding and 5 UTR variants found in macaques that have similar effects on in vitro expression [Vallender et al, 2008] and in behavioral associations [Miller et al, 2004;Barr et al, 2008] as the well-studied A118G variant identified in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been implicated in substance abuse and addiction, including ethanol, cocaine, and heroin [16][17][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%